Post-Cueing Deficits with Maintained Cueing Benefits in Patients with Parkinson’s Disease Dementia - Gräber, Susanne; Liepelt-Scarfone, Inga; Csoti, Ilona; Maetzler, Walter; Sultan, Fahad; Berg, Daniela (Frontiers in Neurology, 2014)
In Parkinson’s disease (PD) internal cueing mechanisms are impaired leading to symptoms such as like hypokinesia. However external cues can improve movement execution by using cortical resources. These cortical processes can be affected by cognitive decline in dementia.It is still unclear how dementia in PD influences external cueing. We investigated a group of 25 PD patients with dementia (PDD) and 25 non-demented PD patients (PDnD) matched by age, sex and disease duration in a simple reaction time (SRT) task using an additional acoustic cue. PDD patients benefited from the additional cue in similar magnitude as did PDnD patients. However, withdrawal of the cue led to a significantly increased reaction time in the PDD group compared to the PDnD patients. Our results indicate that even PDD patients can benefit from strategies using external cue presentation but the process of cognitive worsening can reduce the effect when cues are withdrawn.